Analysis of chemical signatures of alkaliphiles using fatty acid methyl ester analysis - Basha Sreenivasulu; Chinthala Paramageetham; Dasari Sreenivasulu; Bukke Suman; Katike Umamahesh; Gundala Prasada Babu (Wolters Kluwer Medknow Publications, 2017)
Background: Fatty acids occur in nearly all living organisms as the important predominant constituents of lipids. While all fatty acids have essentially the same chemical nature, they are an extremely diverse group of compounds. Materials and Methods: To test the hypothesis, fatty acids of alkaliphiles isolates, Bacillus subtilis SVUNM4, Bacillus licheniformis SVUNM8, Bacillus methylotrohicus SVUNM9, and Paenibacillus dendritiformis SVUNM11, were characterized compared using gas chromatography-mass spectrometry (GC-MS) analysis. Results: The content of investigated ten fatty acids, 1, 2-benzenedicarboxylic acid butyl 2-methylpropyl ester, phthalic acid, isobutyl 2-pentyl ester, dibutyl phthalate, cyclotrisiloxane, hexamethyl, cyclotetrasiloxane, octamethyl, dodecamethyl, heptasiloxane 1,1,3,3,5,5,7,7,9,9,11,11,13,13-etradecamethyl, 7,15-dihydroxydehydroabietic acid, methyl ester, di (trimethylsilyl) ether, hentriacontane, 2-thiopheneacetic acid, undec-2-enyl ester, obviously varied among four species, suggesting each species has its own fatty acid pattern. Conclusions: These findings demonstrated that GC-MS-based fatty acid profiling analysis provides the reliable platform to classify these four species, which is helpful for ensuring their biotechnological interest and novel chemotaxonomic.